Development of pedagogical staff as a constituent part of creating the image of a general secondary educational institution - Tarasenko, I. (Problems of Engineer-Pedagogical Education, 2019)
The article considers the concepts “image” and “image of an educational institution” and presents the components of creating the image of an institution of general secondary education. The emphasis is placed on the fact that, considering the environment of growing competition between educational institutions, the ability of school heads to implement a balanced scientific-based personnel policy is absolutely necessary since it is one of the most important factors influencing the formation of a positive image of an educational institution. The article highlights the expediency of progressive development of pedagogical staff as a key component which forms a favorable image of an institution of general secondary education. The factors influencing the development of pedagogical staff are singled out. The article specifically emphasizes that general secondary education, and thus the promotion of a good image of an educational institution, there can be named staff recruitment, training and advanced training, certification of employees, certification of teachers, staff motivation, creation of proper working conditions, provision of social security, permanent contacts between the leadership and employees of an institution, etc. The paper suggests a model for taking into account the factors which favor the development of pedagogical staff of institutions of general secondary education as a prerequisite for creating a positive image of a general secondary education institution. among the leading factors that impact on the effectiveness of personnel management in institutions of